EVALUATION OF ANGIOGENIC AND WOUND HEALING ACTIVITY OF BERGENIA CILIATA RHIZOME: IN OVO AND IN VIVO STUDY USING HISTOLOGICAL AND ANALYTICAL TOOLS - Uzma Saleem; Fareeha Anwar; Muhammad Ovais Omer; Zaman Khan; Bashir Ahmad; Fiza Saleem; Ahmed Bilal Waqar; Hassan Imran (Journal of Animal and Plant Sciences, 2023)
Bergenia Ciliata(Haw.) Rhizome (B. ciliata R) is used traditionally as a wound-healing remedy in hilly areas of Pakistan. This study was planned to evaluate the angiogenic and wound healing potential of the plant rhizome by in ovo and in vivo methods. For this purpose n-hexane, 80% ethanol-aqueous and aqueous extracts of B. ciliata R were prepared and analyzed for their phytochemical as well as their physicochemical characteristics. The antioxidant potential of all three extracts was determined using DPPH scavenging and Ferric reducing antioxidant power assay (FRAP assay). Based on the antioxidant potential of the extracts 80 % ethanol-aqueous extract was selected for angiogenic and wound healing studies using a Chorioallantoic membrane (CAM) assay and excision wound model, respectively. It was found that the 4 mg/mL 80% ethanol-aqueous extract exhibited the maximum angiogenic activity among all treatments. The macro and microscopic results showed that the 20% ointment accelerated wound healing as compared to the standard therapy and control group. Based upon the results of the CAM assay and excision wound model it is concluded that B. ciliata R extract may possess significant wound healing potential and therefore justify its folklore use as a wound healer.
Keywords: Angiogenesis; wound healing; Bergenia ciliata rhizome; DPPH; FRAP